The effect of sodium borate addition to dimentional stability in type 3 of gypsum - Medina Zahra Ayu Purnama; Benni Benyamin; Shella Indri Novianty (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: The removable dentures or fixed dentures can be used as a replacement for missing teeth and restore the aesthetics and functional condition of the patien. Dentures with good adaptation can be obtained from accurate impressions. Dimensional accuracy and adequate mechanical properties are one of the main requirements of working model making materials. The addition of sodium borate can help gypsum type III achieve balance dimentional stability. The purpose of this study was to determine the difference in dimensional stability of gypsum type III with aquades with the addition of sodium borate and aquades without the addition of sodium borate.Method: Post test only control group design was used as the research design method. This study consisted of 2 groups with a total sample of 32 samples, experimental group with gypsum type III given distilled water with added sodium borate 0.4% and control group with gypsum type III given distilled water without added sodium borate 0.4%. The change of gypsum dimentional stability is measured using digital sliding caliper. Statistical tests were carried out using the Mann Whitney test and the results of the Mann Whitney test were P < 0.05 which means a significant difference between the two groups. Result: The lowest average dimensional change was found in gypsum type III mixed with 0.4% sodium borate.Conclusion: The conclusion of the research is the addition of 0,4% sodium borate solution can help gypsum type III achieve balance dimentional stability.